Identification of the impact of open banking digital infrastructure on financial inclusion in EU countries in the context of macroeconomic and digital development - Maulina, Nurgul; Dutta, Amit; Gabdualiyeva, Raushan; Duissenbayeva, Botagoz; Khamitkhan, Nazgul; Tsaurkubule, Zhanna; Kamali, Karlygash (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study is the financial inclusion in EU countries in the context of macroeconomic and digital development. The problem of quantitatively assessing this relationship in a broad cross-country context has been solved. The following results were obtained: – a significant cross-country divergence was identified in the level of digitalization of the financial sector, the development of ICT (information and communication technologies) infrastructure, and financial inclusion, which forms fundamentally different starting conditions for the implementation of open banking; – a strong positive correlation was established between the level of banking digitalization and the composite financial inclusion index (Pearson’s coefficient +0.894); – an increase in the banking digitalization index by one point leads to an average increase in the composite financial inclusion index by 0.498 points (p < 0.001); – for “leader” countries, the average banking digitalization index was 82.4; for countries with “medium potential” – 61.8; for countries with “basic challenges” – 48.1. The obtained results are explained by the fact that technological development of the financial sector creates prerequisites for reducing transaction costs and the emergence of innovative, non-territorially bound services. The specific features of the results lie in proving the differentiated potential of open banking: for “leader” countries, for countries with “medium potential”, for countries with “basic challenges”. The practical significance of the study lies in providing regulators and financial institutions with quantitatively grounded conclusions for developing differentiated strategies that take into account the level of readiness of the national ecosystem